Precision Packaging and Personalized Medicine: 3D Printing’s Role in Modern Healthcare - Babu, Bachunaga Kishore; Pilli, Daniel; Rao, Podile Venkateswara; Tewari, Veena (International Journal of Pharmaceutical Investigation, 2025)
Background The pharmaceutical industry faces ongoing challenges in mass production, drug personalization, and sustainable packaging. Traditional manufacturing methods often fail to meet the growing demand for tailored therapeutic solutions and eco-friendly packaging alternatives. Emerging technologies like 3D printing hold promise for addressing these limitations through precise drug formulation and innovative packaging solutions. Objectives of the Study The objective of this study is to explore the transformative role of 3D printing in revolutionizing the pharmaceutical industry by advancing personalized medicine and fostering sustainable packaging solutions. Specifically, the study investigates how 3D printing can facilitate the development of bespoke dosage forms tailored to individual patient needs, as well as evaluate its potential to create eco-friendly packaging that ensures drug stability while minimizing environmental impact. Materials and Methods A comprehensive review of the existing literature was conducted to explore 3D printing applications in the pharmaceutical sector. Experimental efforts included developing 3D-printed dosage forms integrating multiple Active Pharmaceutical Ingredients (APIs) tailored to individual patient needs. Biodegradable polymers and diverse 3D printing technologies were utilized to fabricate pharmaceutical dosage forms and packaging prototypes designed to ensure drug stability and sustainability. Results 3D printing demonstrated the ability to produce customized pharmaceutical products with controlled-release mechanisms and multi-drug formulations. Additionally, the 3D-printed packaging prototypes offered enhanced protective qualities and reduced material waste compared to conventional packaging methods. The use of biodegradable polymers further highlighted the environmental benefits of this approach. Findings The study found that 3D printing provides a viable pathway for personalized drug development and sustainable pharmaceutical packaging. These advancements have the potential to transform the pharmaceutical industry by addressing patient-specific requirements and environmental concerns. Conclusion While 3D printing exhibits significant potential in personalized medicine and sustainable packaging, challenges such as regulatory compliance, scalability, and cost-effectiveness remain barriers to widespread adoption. Continued research and development are essential to overcome these hurdles and fully realize the transformative potential of 3D printing in the pharmaceutical sector.
Keywords: 3D Printing; Personalized Medicine; Pharmaceutical Packaging; Drug Customization; Sustainability; Biodegradable Polymers; Precision Dosage Forms